Thermal-fluidic correlations for turbulent flow in a serpentine heat exchanger with novel wing-shaped turbulators. (October 2020) - Liou, Tong-Miin; Chen, Chieh-Chu; Wang, Chun-Sheng; Wang, En-Shou
Highlights: A novel wing-shaped turbulator is proposed for heat transfer elevation. Detailed PIV and IRT measurements of flow and temperature fields are conducted. The correlations of N u ¯ / N u o and f ¯ / f o versus Pi / DH and Re are established. A collection of N u ¯ / N u o − f ¯ / f o data for both previous and present designs is presented. N u ¯ / N u o is able to achieve as high as 5.5 relative to the reported 4.4. Abstract: Turbulent flow structures and heat transfer in a 180-deg sharp turning two-pass internal coolant passage of a serpentine heat exchanger are explored experimentally. The coolant passage has a square cross-section with novel wing-shaped turbulators mounted on two sidewalls. The bulk Reynolds number ( Re ) and pitch ratio ( Pi/DH ) are varied from 5, 000 to 20, 000 and 0.6 to ∞, respectively. It is observed from the Particle Image Velocimetry measurements that there are wing-induced Fujiwhara co-rotating vortices. This unique flow feature leads to an averaged Nusselt number ratio ( Nu ¯ / N u o ) up to 5.5 higher than the highest value of 4.4 reported previously based on the Infrared Thermography results. In addition, the elimination of wake vortices by the present wing-shaped turbulators results in the 61.5% to 66.8% reduction of friction factor ratio ( f ¯ / f o ) compared with the louvered channel. From the thermal-fluidic regression analysis for Pi/DH  = ∞ and 0.7, the dimensionless spanwise-averaged mean transverse velocity and cross-sectionally averaged vorticity magnitude have the high correlation coefficient ( R  ≥ 0.7) with the spanwise-averaged local Nusselt number ratio in both the first and second pass. From the standpoint of thermal performance factor ( TPF ), Pi/DH  = 0.7 is preferable to other values of Pi/DH since it provides the TPF value of 1.68 higher than the previous reported value of 1.41 for 15 ≤ f ¯ / f o ≤ 80. Finally, empirical correlations of Nu ¯ / N u o and f ¯ / f o versus Re and Pi/DH are proposed.